The Integration of Entertainment and Education: An Exploration of the Narrative Rhetoric of TCM Knowledge Dissemination in Legend of Zhen Huan - Chen, Shuyi (Transactions on Social Science, Education and Humanities Research, 2026)
Traditional Chinese Medicine (TCM) represents a profound repository of ancient wisdom, encompassing unique philosophical frameworks, diagnostic methodologies, and health-preserving practices. However, its inherent complexity-rooted in abstract concepts and specialized principles-and cultural distinctiveness have long hindered its widespread accessibility to the general public. In the context of knowledge dissemination, film and television works have emerged as pivotal carriers, leveraging audio-visual storytelling to transform esoteric professional content into intuitive, engaging narratives. Among such works, the TV drama Legend of Zhen Huan has achieved remarkable success in popularizing TCM knowledge: by seamlessly integrating medicinal properties, dietary health preservation, and TCM therapies into its plotlines, it has made complex TCM concepts perceptible and memorable to a broad audience, setting a notable example for the public communication of specialized medical knowledge. Given the growing significance of media in shaping public understanding of traditional health systems, exploring how the drama achieves accessible TCM dissemination through narrative strategies holds substantial value for both cultural communication and health education research.